Pediatric necrotizing pneumonia case report: clinical features, treatment experience, and prospects - Zhang, Jingli; Zhang, Yingqian; Duan, Chenchu; Zhang, Tengteng; Zhao, Yujing; Zhen, Lina (Frontiers in Medicine, 2025)
Necrotizing pneumonia (NP) is a rare but severe complication of community-acquired pneumonia in children, often mimicking Congenital Pulmonary Airway Malformation and presenting significant diagnostic and therapeutic challenges. We report the case of a 2-year-old boy with a prolonged and complex course of NP, initially suspected to have Congenital Pulmonary Airway Malformation. The patient presented with persistent fever, cough, and dyspnea, accompanied by co-infections with Streptococcus pneumoniae, influenza A (H3N2), human metapneumovirus, and Mycoplasma pneumoniae. Imaging revealed progressive lung consolidation evolving into cavitary lesions and pneumothorax. Laboratory tests showed leukopenia with a left shift, neutrophil toxic changes, and reduced CD3+, CD8+ T cells, NK cells, and IgG levels, suggestive of secondary immunosuppression, although an inborn error of immunity could not be fully excluded. Given the patient’s age and ongoing lung development, conservative management with targeted anti-infective therapy and supportive care was prioritized over surgical resection. By 9 months of follow-up, the cavitary lesions had almost completely resolved, whereas persistent bronchiectasis was still evident at 17 months. The child remained clinically well without recurrent infections. This case underscores that leukopenia does not rule out bacterial infection, particularly in the presence of left shift and neutrophil toxic changes. It highlights the importance of immunologic evaluation, vaccination against pneumococcus and influenza, long-term imaging follow-up, and cautious consideration of surgery in young children with NP.